The impact of sign language exposure and use in deaf children's acquisition of vocabulary / Chong Vee Yee - Chong, Vee Yee (2012)
This research studies the expressive and receptive skills of four Deaf children with the aim of investigating how different linguistic environment, such as the amount of input and practice, will affect their sign language acquisition. The study was conducted through observations of the subjects in the formal learning activity sessions and their regular activities in three different settings: home, church and shopping mall. Interviews were conducted with each of the subjects’ parents to gather background information regarding the linguistic input the subjects have acquired as well as the way the subjects communicate with their parents and the people around them. During the observation period in the learning activities, the subjects’ expressive and receptive levels in sign language through their responses to the Early Intervention Programme (EIP) worker were videotaped, and later transcribed orthographically for further analysis. Analyses show that the subjects are capable in expressing sign language vocabulary based on the amount of input the subjects had acquired from their parents and practiced. This is in line with Watson, Watson and Wilson (1999)’s recommendation that sufficient input and practice is important in acquiring language. The handshapes that the subjects formed and are able to recall reflect the time and effort the subjects have taken to practice the sign vocabularies in communicating with the people around them. This study hopes to pave the way to greater initiative and interest in sign language related research in Malaysia, especially in the field of sign language acquisition that affects all Deaf people.